Health and Socioeconomic Status: Examination of Differences in Socioeconomic Status According to Some Health Indicators - İhsan Kutlu (İnsan & Toplum)
Health is open to the influence of many social factors, and when the distribution of health within the social structure is examined, it appears that it differs with socioeconomic status. In this context, the subject of the study was determined as the relationship between socioeconomic status and health / disease. The aim of the study is to examine the differentiation of the socioeconomic status variable among people according to health indicators. A cross-sectional relational screening was carried out with a quantitative research method. The universe of the study is over 18 years of age the urban population in Turkey 2018. At the NUTS 1 level, a total of 730 participants were reached in 12 provinces based on addresses, but the socioeconomic status scores of 648 people could be calculated. In the study, the TUSES (Turkey Socioeconomic Status) Scale was used to measure socioeconomic status as well as the question form with various health-related questions as a data collection tool. Descriptive statistics for introducing the characteristics of the people reached in the research; Independent groups t test, one-way analysis of variance and multiple comparison tests were used to demonstrate health and socioeconomic status differentiation. As a result of the examinations, differences were found between some health indicators and socioeconomic status, and it was seen that people who were positive in terms of health indicators also had better scores in terms of socioeconomic status. Considering the relation of health with socioeconomic status, it is suggested that the social dimension of health should be brought to the fore and that holistic social policies should be developed in order to distribute health in a more balanced way in social life.